The effect of longitudinal spin-fluctuations on high temperature properties of Co3Mn2Ge. (15th March 2023) - Delczeg-Czirjak, Erna K.; Eriksson, Olle; Ruban, A.V.
Abstract: It is demonstrated that thermally induced longitudinal spin fluctuations (LSF) play an important role in itinerant Co3 Mn2 Ge at an elevated temperature. The effect of LSF is taken into account during ab initio calculations via a simple model for the corresponding entropy contribution. We show that the magnetic entropy leads to the appearance of a medium size local moment on Co atoms. As a consequence, this leads to a renormalization of the magnetic exchange interactions with a quite substantial impact upon the calculated Curie temperature. Taking LSF into account, the calculated Curie temperature can be brought to be in good agreement with the experimental value. Graphical abstract: